Navigating Sexism in the Workplace: A Comparative Study of Muslim and Buddhist Female Workers in Malaysia - Binti Hamit, Anis Aqilla; Ramadhan, Ramadhan (Prodi Studi Agama-Agama, 2024)
This study explores the widespread issue of sexism in Malaysia, focusing on its impact on Muslim and Buddhist female workers. Employing a qualitative approach, the research involves observations, interviews, and documentation to examine how sexism affects women's job opportunities across various sectors. The findings reveal that despite legal progress, sexism remains deeply ingrained, manifesting through discriminatory practices that impede women’s professional advancement and reinforce gender stereotypes. Muslim women encounter additional challenges related to compliance with Islamic teachings in the workplace, while Buddhist women face cultural prejudices that impact their employment opportunities. This study contributes to the gender equality discourse by providing insights into the specific experiences of women in Malaysia, highlighting the need for targeted interventions to combat sexism and promote a more equitable society.